2021
DOI: 10.7602/jmis.2021.24.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and long-term implications of unplanned conversion during laparoscopic liver resection for hepatocellular carcinoma located in anterolateral liver segments

Abstract: Purpose The impact of conversion on perioperative and long-term oncologic outcomes is controversial. Thus, we compared these outcomes between laparoscopic (Lap), unplanned conversion (Conversion), and planned open (Open) liver resection for hepatocellular carcinoma (HCC) located in anterolateral (AL) liver segments and aimed to identify risk factors for unplanned conversion. Methods We retrospectively studied 374 patients (Lap, 299; Open, 62; Conversion, 13) who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In this study, the surgical outcomes following UPC included greater intraoperative blood loss, greater transfusion requirements, longer hospital stay, and increased morbidity compared with LLR, consistent with the results of previous studies [9,[21][22][23]. These results are somewhat predictable because the most common reason for UPC is uncontrolled bleeding during LLR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the surgical outcomes following UPC included greater intraoperative blood loss, greater transfusion requirements, longer hospital stay, and increased morbidity compared with LLR, consistent with the results of previous studies [9,[21][22][23]. These results are somewhat predictable because the most common reason for UPC is uncontrolled bleeding during LLR.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the impact of conversion to open surgery on long-term outcomes remains controversial. Several studies have demonstrated that conversion to open surgery may be associated with adverse long-term oncologic outcomes in laparoscopic colorectal surgery [7][8][9]. However, other studies have reported similar oncological outcomes after colectomy between converted and non-converted patients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…No information was given on preoperative chemoembolization, radiofrequency ablation, or percentage of conversion from laparoscopic to open surgery. As it has been already shown by Shin et al , patients who experienced unplanned conversion during LLR showed poor perioperative and long-term outcomes compared to those who underwent planned laparoscopic and OLR ( 12 ).…”
mentioning
confidence: 88%
“…As in this study [ 3 ], one of the most important reasons for conversion to open surgery is bleeding during surgery, and the causes of bleeding are various, such as the size, location, and number of tumors, and the degree of cirrhosis of the liver. Minimizing bleeding and, if there is bleeding, quick hemostasis can help to reduce unplanned conversion to open surgery [ 4 6 ].…”
mentioning
confidence: 99%